2020
DOI: 10.3389/frobt.2020.558027
|View full text |Cite
|
Sign up to set email alerts
|

Model Reference Predictive Adaptive Control for Large-Scale Soft Robots

Abstract: Past work has shown model predictive control (MPC) to be an effective strategy for controlling continuum joint soft robots using basic lumped-parameter models. However, the inaccuracies of these models often mean that an integral control scheme must be combined with MPC. In this paper we present a novel dynamic model formulation for continuum joint soft robots that is more accurate than previous models yet remains tractable for fast MPC. This model is based on a piecewise constant curvature (PCC) assumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…A different approach uses an energy-shaping approach to develop the control law for a soft continuum manipulator [120]. MPC is another technique that was employed for the control of largescale soft robots [121]. The MPC algorithm relies on a PCC model alongside a kinematic representation for efficient state prediction.…”
Section: Controlmentioning
confidence: 99%
“…A different approach uses an energy-shaping approach to develop the control law for a soft continuum manipulator [120]. MPC is another technique that was employed for the control of largescale soft robots [121]. The MPC algorithm relies on a PCC model alongside a kinematic representation for efficient state prediction.…”
Section: Controlmentioning
confidence: 99%
“…An analytical equation of motion of the form shown in Equation (1) can be derived using principles of Lagrangian mechanics by modeling the joint as an infinite set of infinitesimally thin disks and integrating along the length of a piecewise constant curvature (PCC) arc. This method was developed in Hyatt et al ( 2020a ), which includes a detailed derivation of this model.…”
Section: First Principles and Deep Learningmentioning
confidence: 99%
“…While previous work (Hyatt et al, 2020a ) demonstrated that this formulation of the dynamic model was accurate enough for model-based control, improvements are needed in order to control soft robots in uncertain environments or during highly dynamic movements. Certainly, further system identification would improve this model; however, because of the complexities and uncertainties inherent in soft robots and the processes to manufacture them, system identification techniques scale poorly with high degree-of-freedom systems and do not necessarily generalize well between platforms.…”
Section: First Principles and Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach based on sliding mode and fuzzy control is applied in [29] for a rotary actuator with elastic chambers. Model predictive control based on learned nonlinear models as applied in [30] can also be combined with ideas from adaptive control to compensate for model deviations, as presented in [31]. The authors of [32] use reinforcement learning to control a system that is jointly actuated with tendons and pneumatic actuators.…”
Section: Related Workmentioning
confidence: 99%